The Effectiveness of a Group Counseling Program on ‎Reducing Test Anxiety and Improving Study Habits ‎Among a Sample of High Achievers at the Faculty of ‎Education- Najran University - Hamadneh, Burhan (Jordan Journal of Educational Sciences, 2017)
The aim of the study was to examine the effectiveness of a group counseling program in reducing anxiety test and improving study habits among a sample of high achievers at the faculty of education- Najran University. The sample of the study consisted of (20) students assigned equally into two groups: control group (N=10) having no treatment, and an experimental group (N=10) having a group counseling treatment program. For data collection, the researcher developed a anxiety test scale and study habits scale. Both validity and reliability were obtained for the Saudi university students. The most significant results of the study were that the group counseling program was effective in reducing anxiety and improving study habits among experimental group students. The study recommended the need for urging academic counseling departments in universities to employ group counseling programs while working with high achievers and average students